Human Resource Management is a Prerequisite for Enhancing the Quality of Higher Education in Kosovo - Nallbani, Shqiponja (European Journal of Multidisciplinary Studies, 2016)
Given its problematic past, Kosovo’s economic and social development and its current resolve for a European integration process, will be a challenge that will follow for a long time. Because of the burden that state institutions carry in this mission, it is easily verifiable that the process of reform of public administration staff, both at local and central level, is failing. This is primarily because their number is too large and the government has no plans to either reduce this number or to increase their capacity and competence through educational programs of higher education. So far, the Kosovo government, specifically the Ministries of Education, Social Welfare, Labor, etc., and the local governments have no plans on how to achieve this task and the providers of higher education have not provided any program that would adequately enable employees to get re-qualified, in order to carry out their public duties more efficiently and professionally. Therefore, the requalification of staff at a higher education level is one of the essential factors that should be implemented immediately.
Keywords: Requalification, education, public administration, learning programs JEL: I2; I25; I30; J2; J24